Mining Noise Pollution: A Case Study of a Crushing Plant in Sintang - Meilasari, Fitriana; Sutrisno, Hendri; Ningrum, Gemilang Oktavia; Aprillia, Ricka; Kurniawan, Eddy (Universitas Diponegoro, 2025)
The crushing plant in the mining industry produces noise levels above the allowable noise level, potentially causing hearing damage to mining workers. One way to early control this is by mapping the noise distribution in the area. The noise distribution mapping was based on noise intensity. The noise intensity measurement was done using a sound level meter according to Indonesian national standards 7231:2009. The noise exposure analysis was based on the NIOSH formula and Indonesia's national standard 7570:2023. The study's results revealed that noise levels at the source exhibited an intensity of approximately 95-103 dB. The noise propagation pattern extended from the southwest to the northeast, with an intensity of approximately 68-93 dB. The highest noise intensity was observed in the vicinity of the first jaw crusher, exceeding 100 dB, with a daily exposure time in this area of 6-12 minutes. Prolonged exposure to high noise levels can potentially lead to auditory damage. Therefore, the implementation of noise control measures, including using personal protective equipment and the installation of appropriate safety signage, is imperative.